PEBP1 Regulates Ferroptosis in Acute Glaucoma: Targeted Therapy Using Engineered Exosomes - Yijia Huang; Di Gong; Junhong Guo; Wei Huang; Tingyu Hu; Shengbin Tang; Li Li; Bingkai Feng; Kuanrong Dang; Simin Deng; Yong Liu; Chunyan Tan; et al. (The FASEB Journal, 2026)
ABSTRACT Glaucoma is the leading cause of irreversible blindness worldwide, primarily driven by the progressive loss of retinal ganglion cells (RGCs) under pathological high intraocular pressure (ph‐IOP). Despite the established role of ferroptosis in RGC degeneration, specific molecular targets that can be used for clinical intervention still need to be optimized, and the slow onset of conventional gene therapy vectors is incompatible with the acute clinical course of glaucoma. Here, we integrate single‐cell RNA sequencing and spatial transcriptomics to profile the dynamic transcriptomic landscape of the rat retina across acute, subacute, and chronic stages of ph‐IOP injury. Through ferroptosis‐focused screening of an early‐activated RGC gene cluster, we identify the lipid metabolism regulator phosphatidylethanolamine‐binding protein 1 (PEBP1) as a candidate mediator of RGC ferroptosis. We demonstrate that Pebp1 is specifically upregulated in injured RGCs with a trajectory mirroring ferroptosis pathway activation, and that AAV‐mediated Pebp1 knockdown suppresses ferroptosis through the GPX4/ACSL4 signaling axis, thereby preserving RGC survival, retinal structure, and visual function. To overcome the critical time‐window bottleneck—the several weeks delay required for AAV‐mediated silencing versus the rapid, irreversible RGC loss in acute glaucoma—we engineer Exosomes‐siPebp1, a mesenchymal stem cell‐derived exosome system loaded with siPebp1, which enables immediate single‐dose intervention post‐injury. This system exhibits efficient RGC uptake, prolonged intraocular retention, and robust target gene silencing, and, in a head‐to‐head comparison, significantly outperforms unloaded exosomes, liposomal formulations, and AAV vectors in RGC protection, without detectable acute systemic or local toxicity. Collectively, this study implicates Pebp1 in ph‐IOP‐associated RGC ferroptosis and supports exosome‐mediated siRNA delivery as a rapid, cell‐free intervention strategy for acute glaucomatous injury.